Yung Kee: Resolving corporate governance troubles in a Hong Kong-based family business - YANG, Holly (Institutional Knowledge at Singapore Management University, 2021)
This case describes the trials and tribulations that tested Yung Kee Restaurant, a Chinese roast goose restaurant in Hong Kong. The former Michelin-star eatery, founded by Kam Shui-fai, received several other accolades, including recognition by Fortune magazine as one of the world’s best restaurants. Unfortunately, with the passing on of Kam Senior in 2004, a bitter feud over the ownership and management of Yung Kee erupted among his children; the public dispute tore the family apart. At one point, Kam family members refused to even acknowledge one another in social settings. In July 2010, the elder Kam brother, Kinsen, applied to the Hong Kong High Court to liquidate Yung Kee Holdings, if his younger brother, Ronald, refused to buy out his stake. In 2015, the court instructed Yung Kee Holdings to close its business, which could spell the end of the restaurant, which was its crown jewel and a culinary institution in the city. Fast forward to 2020, Yung Kee has survived the ordeal. A third-generation member of the Kam family became Chief Financial Officer (CFO) of the restaurant and helms the family business. What could have been done better in terms of corporate governance? In what other ways could the family business be organised? Students should be able to 1) recognise, explain, and interpret the concepts, framework, and principles that underlie corporate governance guidelines and practices, 2) identify and analyse the internal governance environment and risk factors of firms, in particular family businesses, 3) explain and evaluate the roles and responsibilities of boards of directors and the composition and structure of the board, and 4) understand the importance of leadership succession, particularly in family firms.